DAKWAH KULTURAL DAN ISLAMISASI DI TERNATE - Sariyah Ipaenin (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2018)
This article presents a study of the beginning of the cultural propagation movement amid Ternate society which still adheres to animist beliefs and dynamism. The spread of da'wah in Ternate cannot be separated from the Islamization process carried out by Arabs and Persians who trade and establish marriage ties with local communities. These immigrant community groups preach through cultural approaches by utilizing culture as a means, media, and targets. Cultural propaganda has the object of the majority of people who do not know Islam well. If they are familiar with Islam, the common goal is enthusiasm for culture and previous myths that still adhere to strong beliefs. The role and effectiveness of cultural dakwah are needed for the success of the Islamic mission in Indonesia, especially for the people of Ternate.